ANALISIS BIAYA DAN GAMBARAN PENGGUNAAN ANTIBIOTIK PADA PASIEN DEMAM TIFOID RAWAT INAP DI PUSKESMAS TLOGOSARI KULON TAHUN 2007 - mohammad djatmiko; sugiyanti sugiyanti; yance anas (Universitas Wahid Hasyim Semarang, 2008)
ABSTRACTThyfoid fever is a suddenly fever causing by Salmonella Typhii infection. Pharma coeconomi research can help pharmacologist and nursing for deciding exact and efficient antibiotic medicine using. Direction of this research showing description of antibiotic using which consist of choosing group and type of antibiotic, single or combination using, oral on injection antibiotic supply, identification of component and therapy cost, calculating medicine using cost comparison against therapy cost on typhoid fever room caring patient in Puskesmas Tlogosari Kulon on 2007. This research is retrospective with descriptive data analysis. Data taken from 183 medical report of room caring typhoid fever patient on Puskesmas Tlogoari Kulon on 2007. Information from medical record is patient identity, medicine therapy, laboratory and caring time. Therapy cost counted from healthy tariff service book of Puskesmas Tlogosari Kulon. The result of research showing description of antibiotic using in typhoid fever room caring on Puskesmas Tlogosari Kulon on 2007 consist of : the most antibiotic used penisilin 40,45%, kuinolon 23,16%, kloramfenikol 22,64% the most antibiotic used ampisilin 34,35%, siprofloksasin 23,16%, kloramfenikol 17,81%, the most single giving antibiotic is kloranfenikol 5,15%, siprofloksasin 4,46%, combination antibiotic is ampisilin and siprofloksasin 26,80%, ampisilin and kloramfenikol 15,98%, the most givig way is oral combination and injection 82,52%,. Component and therapy cost of typhoid fever patient consist of : antibiotic cost Rp. 87.404,- non antibiotic cost Rp. 104.168,- accommodation and administration Rp.85.131,- visit cost or medician visit consultation Rp. 31.902,- act cost Rp. 25.306 and supporting checking cost Rp. 37.279. Medicine using cost comparison is 51,61% against total therapy cost Rp. 371.189,- Key word : cost analysis, tifoid fever, Puskesmas Tlogosari Kulon